PENGARUH FINANCIAL DISTRESS, KONSERVATISME, DAN SALES GROWTH TERHADAP TAX AVOIDANCE PERUSAHAAN (Studi Empiris pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2017-2019) - Renaldi Alfarasi; Dul Muid (Diponegoro Journal of Accounting, 2022)
This study aims to examine the influence of financial distress, conservatism, and sales growth on corporate tax avoidance practices. The independent variable of this study is financial distress, conservatism, and sales growth, whereas tax avoidance as the dependent variable. This research used the food and beverage companies sample that listed in Indonesia Stock Exchange on 2017-2019 period. This study is a quantitative study using secondary data in the form of annual reports 20 companies for 3 years. The sampling method used in the study is purposive sampling. The hypotheses testing used multiple regression analysis with the help of SPSS version 22 software. The results of this study show that financial distress, conservatism and sales growth have significant effect on tax avoidance.